2013
DOI: 10.1007/s11883-012-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carotid Intimal Thickness Testing and Risk Prediction in the Development of Coronary Atherosclerosis

Abstract: Carotid Ultrasound is a safe and available non invasive diagnostic tool that provides information about the carotid arteries’ characteristics and may be used for early detection of coronary artery disease as well as cardiovascular and stroke event risk stratifications. We performed a systematic search of the articles discussing carotid ultrasound in English literature, published in PubMed from the year2010 to September 2012. Generally, the studies showed that Internal carotid artery intima media thickness is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 20 publications
0
40
1
7
Order By: Relevance
“…Carotid intima media thickness (CIMT) was measured 1.0 cm distal to both common carotid artery bifurcations. The presence of carotid artery plaque was determined when the local CIMT was ≥ 1.5 mm or 50% of the surrounding area 17) .…”
Section: Methodsmentioning
confidence: 99%
“…Carotid intima media thickness (CIMT) was measured 1.0 cm distal to both common carotid artery bifurcations. The presence of carotid artery plaque was determined when the local CIMT was ≥ 1.5 mm or 50% of the surrounding area 17) .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, for men, cIMT progression rate was 33% higher (0.020 mm/year) compared to females (0.015 mm/year). Darabian et al reported a higher contribution due to chronological age in the progression of cIMT in both CCA (0.007 mm/year) and ICA (0.037 mm/year). Kasliwal et al reported a study of Asian Indian ethnicity with larger CCA IMT progression rate in females (0.014 mm/year) compared to males (0.01 mm/year).…”
Section: Discussionmentioning
confidence: 97%
“…The Tunica Intima, made up of endothelial cells, and the Tunica Media comprised of smooth muscle, line the entire inside structure of arteries and veins. The thickness of the Tunica Intima and the Tunica Media of the carotid artery (Intima Media Thickness-IMT) are reliable indicators of the presence and severity of CVD [9,10]. Chronic high plasma fibrinogen levels have a strong relationship with the severity of IMT [11].…”
Section: Fibrinogen Overviewmentioning
confidence: 99%